상급초보간호사의 간호전문직관, 프리젠티즘, 직무착근도의 관계 - 김영은(Young-Eun Kim); 박소현(So-Yeon Park); 강혜원(Hye-Won Kang) (인문사회과학연구, 2024)
· 연구 주제: 상급초보간호사를 대상으로 간호전문직관 프리젠티즘, 직무착근도의 관계를 확인하여 상급초보 간호사들의 직무착근도를 향상시키기 위한 프로그램의 개발을 위한 기초자료를 제공하고, 상급초보 간호사 전문인력 확보 및 높은 간호의 질로 환자 간호를 제공하도록 하는 근거를 마련하고자 한다. · 연구 배경: 코로나19 이후 간호사 인력 부족과 처우 개선 문제가 부각되면서, 특히 숙련된 간호인력을 확보하는 것이 중요한 과제로 떠올랐다. 상급초보간호사(경력 1~3년 차)는 전문직관 발달 초기 단계에 있으며, 이들은 높은 이직률, 직무 스트레스, 프리젠티즘으로 인해 조직에 머무는 데 어려움을 겪는다. 직무착근도는 간호사의 직무 만족과 이직률에 중요한 영향을 미치는 요소로, 본 연구는 상급초보간호사의 간호전문직관, 프리젠티즘, 직무착근도의 관계를 확인하고, 이들의 직무착근도를 향상시키기 위한 방안을 모색하는 것을 목적으로 한다. · 선행연구와의 차이점: 본 연구는 기존 연구와 다음과 같은 차별성을 지닌다. 첫째, 신규 간호사나 경력 간호사가 아닌 상급초보간호사를 대상으로 간호전문직관, 프리젠티즘, 직무착근도의 상관관계를 심층 분석하였다. 둘째, 프리젠티즘이 직무착근도에 미치는 부정적 영향을 명확히 규명하여 간호사들의 직무 만족도와 조직 몰입에 대한 중요한 요인을 제시하였다. 셋째, 프리젠티즘과 간호전문직관 간의 음의 상관관계를 밝혀, 프리젠티즘이 간호사들의 직업적 자부심과 직무 성취감에 부정적 영향을 미친다는 점을 강조하였다. · 연구방법: 연구 대상은 S시 소재 종합병원에서 근무하는 임상경력 13개월 이상 36개월 이하의 상급초보간호사 96명으로, 부적절한 응답 8부를 제외한 83부를 최종 분석에 사용하였다. 자료 분석은 SPSS/WIN 27.0 프로그램을 이용하였으며, 기술통계는 실수, 백분율, 평균, 표준편차로 분석하였다. 간호전문직관, 프리젠티즘, 직무착근도의 차이는 t-test, ANOVA, 그리고 사후 검증을 위해 Tukey HSD를 사용하였고, 상관관계는 Pearson's Correlation Coefficients로 분석하였다. · 연구결과: 본 연구결과 직무착근도와 간호전문직관은 유의한 양의 상관관계(r=.343, p<.002), 직무착근도와 프리젠티즘은 유의한 음의 상관관계(r=-.484, p<.000), 그리고 프리젠티즘과 간호전문직관은 유의한 음의 상관관계(r=-.333, p<.002)가 있는 것으로 나타났다. 본 연구는 상급초보 간호사들의 직무착근도를 향상시키기 위해서는 간호전문직관을 높이고 프리젠티즘을 줄이는 것이 중요하다는 점을 강조한다. 이를 위해 간호사들의 직업에 대한 긍정적 인식을 강화하는 교육 프로그램의 도입과, 프리젠티즘을 예방하고 관리할 수 있는 병원 내 제도적 지원이 필요하다. 이를 통해 상급초보 간호사들이 조직 내에서 지속적으로 근무하며 전문 역량을 발휘할 수 있는 환경을 조성할 수 있을 것이다. · 공헌점 및 기대효과: 본 연구는 상급초보간호사에 대한 연구가 미비한 가운데 간호전문직관, 프리젠티즘, 직무착근도와의 관계를 확인하였으며, 상급초보간호사들의 직무착근도를 향상시키기 위한 프로그램의 개발을 위한 기초자료를 제공하고, 상급초보간호사 전문인력 확보를 위한 근거자료로 활용할 수 있다는 데에 의의가 있다. · Research Topic: By identifying the relationship between nursing professional presenteeism and job embeddedness for senior beginner nurses, we intend to provide basic data for developing programs to improve job embeddedness for senior beginner nurses and to provide patient care with high-quality care. · Research Background: The shortage of nursing staff and the issue of improving working conditions have come to the forefront following the COVID-19 pandemic, making the retention of experienced nurses a critical task. Advanced beginner nurses (with 1 to 3 years of experience) are in the early stages of developing their professional skills. However, they face challenges in staying within organizations due to high turnover rates, job stress, and presenteeism. Job embeddedness is a crucial factor that influences job satisfaction and turnover rates among nurses. This study aims to examine the relationship between advanced beginner nurses' perceptions of the nursing professional, presenteeism, and job embeddedness, and seeks to propose measures to enhance their job embeddedness. · Differences from previous studies: This study has the following differences. First, the correlation between nursing professionals, presenteeism, and job embeddedness was analyzed in depth for senior beginner nurses who are not new or experienced. Second, important factors for nurses' job satisfaction and organizational commitment were presented by clearly identifying the negative effects of presenteeism on job embeddedness. Third, by revealing a negative correlation between presenteeism and nursing professionals, it was emphasized that presenteeism negatively affects nurses' professional pride and job achievement. · Research method: The study subjects were 96 senior beginner nurses with 13 months or more and 36 months or less of clinical experience working at a general hospital in S city, and 83 copies were used for the final analysis, excluding 8 inappropriate responses. Data analysis was performed using the SPSS/WIN 27.0 program, and descriptive statistics were analyzed as real numbers, percentages, means, and standard deviations. Differences in nursing professional intuition, presenteeism, and job embeddedness were t-test, ANOVA, and Tukey HSD for post-testing, and Pearson's Correlation Coefficients analyzed correlation. · Research results: As a result of this study, there was a significant positive correlation between job rootedness and nursing professional staff (r=.343, p<.002), a significant negative correlation between job rootedness and presenteeism (r=-.484, p<.000), and a significant negative correlation between presenteeism and nursing professional staff (r=-.333, p<.002). This study emphasizes the importance of increasing nursing professionals and reducing presenteeism to improve the job rootedness of advanced novice nurses. To this end, it is necessary to introduce an educational program that strengthens the positive perception of nurses' jobs and provides institutional support in hospitals to prevent and manage presenteeism. Through this, it will be possible to create an environment where advanced novice nurses can continue working within the organization and demonstrate their professional capabilities. · Contributions and expected effects: This study is meaningful in that it confirms the relationship between nursing professionals, presenteeism, and job attendance amid insufficient research on senior beginner nurses, provides basic data for the development of programs to improve job attendance for senior beginner nurses, and can be used as a basis for securing professional workers for senior beginner nurses. KCI Citation Count: 0